The moderating role of online booking on the effects of digital marketing and dynamic pricing on customer satisfaction and hotel performance: Evidence from three-star hotels in Bali - Sugiarto, Ismoyo; Brahmasari, Ida Aju; Ratih, Ida Aju Brahma (Edelweiss Applied Science and Technology, 2025)
This study aims to examine the influence of digital marketing and dynamic pricing on customer satisfaction and hotel performance, with customer satisfaction serving as a mediating variable and online booking as a moderating variable. The research focuses on three-star hotels in Bali Province to understand the effectiveness of digital marketing strategies and price flexibility in enhancing customer experience and hotel performance amid increasingly dynamic industry competition. A quantitative approach was employed through a survey of managers of three-star hotels registered with hotel associations in Bali. The data were analyzed using PLS-SEM to test the direct, mediating, and moderating effects within the research model. In addition, IPMA was utilized to identify managerial priorities in improving variables that contribute to hotel performance. The findings reveal that dynamic pricing significantly influences customer satisfaction and hotel performance, while digital marketing does not show a direct effect on satisfaction. Customer satisfaction is confirmed to be an important mediator in improving hotel performance. Furthermore, online booking strengthens the effect of dynamic pricing on satisfaction but does not moderate the impact of digital marketing. These results offer practical implications for hotel management to prioritize customer satisfaction, optimize data-driven dynamic pricing strategies, and ensure effective integration between digital strategies and online booking systems to enhance long-term competitiveness.